Reduced cerebellar neurodegeneration after combined therapy with cyclodextrin/allopregnanolone and miglustat in NPC1: A mouse model of Niemann‐Pick type C1 disease. Issue 3 (14th November 2014) - Maass, Fabian; Petersen, Jana; Hovakimyan, Marina; Schmitt, Oliver; Witt, Martin; Hawlitschka, Alexander; Lukas, Jan; Rolfs, Arndt; Wree, Andreas
Abstract : Niemann‐Pick type C1 (NPC1) disease is a lysosomal storage disease characterized by a deficiency of NPC1 gene function. The malfunction of protein results in a progressive accumulation of lipids in many organs. A combined approach with substrate‐reduction therapy (SRT) and byproduct therapy (BPT) has been shown to ameliorate the disease course in a mutant mouse model (NPC1 –/– ). The present study examines the morphological parameters underlying these changes. For the combined SRT/BPT treatment, NPC1 –/– mutant mice (NPC1 –/–SRT/BPT ) were injected with allopregnanolone/cyclodextrin weekly, starting at postnatal day (P) 7. Starting at P10, a miglustat injection was administered daily until P23. Thereafter, miglustat was added to the powdered chow. For the sham treatment, both mutant NPC1 –/– (NPC1 –/–sham ) and wild‐type (NPC1 +/+sham ) mice received an NaCl injection and were fed powdered chow without miglustat. Analysis was performed on cerebellar slices by histology and immunohistochemistry. The volumes and cell counts of cerebellar structures were quantified. Additionally, ultrastructural analysis was performed with transmission electron microscopy. In agreement with previous studies, the current study demonstrates Purkinje cell degeneration in the mutant mice, which was partially abrogated by SRT/BPT. The volumes of cerebellar white matter and molecular layer were reduced as well. Also, the number of neurons was reduced in granular and molecular layers. However, only the molecular layer benefited from the therapy, as shown by an increase in the volume and the amount of neurons. The volume and number of neurons of the deep cerebellar nuclei were significantly decreased in mutant mice; an appreciable therapeutic benefit could be demonstrated for the nucleus interpositus. © 2014 Wiley Periodicals, Inc.